Gall inducing jumping plant lice of the genus Nothotrioza Burckhardt (Hemiptera: Psylloidea: Triozidae) associated with Myrtaceae. Issue 13 (18th April 2022) - Burckhardt, Daniel; Carneiro, Renê G.S.; Fernandes, Ivonette S.; de Queiroz, Dalva L.
ABSTRACT: Nothotrioza is a small genus of jumping plant lice comprising three described species in Brazil and one in the USA (Florida) that induce galls on the leaves of their myrtaceous hosts. The galls of the Brazilian species are globoid and associated with Psidium spp.; those from Florida are pouch galls on Mosiera . Here we describe two new species from Brazil, Nothotrioza acuminata Burckhardt sp. nov. from Psidium laruotteanum and N. camptyla Burckhardt sp. nov. from P. rufum . Both species induce globoid galls similar to those of the other Brazilian species. The new taxa are diagnosed and illustrated, and identification keys for adults and the last-instar immatures are provided for all known species. The presence of mummies in the material of the new species suggests that they are as heavily parasitised as reported for the Brazilian species N. cattleiani Burckhardt and N. myrtoidis Burckhardt. Our data suggest that Nothotrioza species are monophagous with narrow geographical ranges. http://www.zoobank.org/urn:lsid:zoobank.org:pub:8C775EEA-461F-40CD-8570-E55307FAEDE4 http://www.zoobank.org/urn:lsid:zoobank.org:pub:CE1B1065-23B6-4A22-A7F8-70FA1A9B362B http://www.zoobank.org/urn:lsid:zoobank.org:pub:7CFA3D7C-C27B-4973-8708-91844F5F4D55